The Influence of the Mappasikarawa Tradition on the Level of Compliance with Customs and Islamic Law in Bugis-Makassar Marriages - Adi Nugraha; Kartika Putri (Indonesian Journal of Islamic Law, 2022)
This research examines the influence of the Mappasikarawa tradition in Bugis-Makassar marriages on the level of compliance with Islamic customs and law. Qualitative methods with a phenomenological approach are used to understand in depth the implementation of this tradition. Data was collected through in-depth interviews, direct observation and document analysis. The research results show that the Mappasikarawa tradition has a significant influence on compliance with Islamic customs and laws in marriage. Factors such as economics, education, and social changes influence the implementation of this tradition. However, the involvement of traditional leaders and ulama helps maintain traditional values and Islamic law in implementing the Mappasikarawa tradition.